2013
DOI: 10.1103/physreva.88.053625
|View full text |Cite
|
Sign up to set email alerts
|

Hard-core bosons in a zig-zag optical superlattice

Abstract: We study a system of hard-core bosons at half-filling in a one-dimensional optical superlattice. The bosons are allowed to hop to nearest and next-nearest neighbor sites. We obtain the ground state phase diagram as a function of microscopic parameters using the finite-size density matrix renormalization group (FS-DMRG) method. Depending on the sign of the next-nearest neighbor hopping and the strength of the superlattice potential the system exhibits three different phases, namely the bond-order (BO) solid, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 30 publications
(34 reference statements)
0
20
0
Order By: Relevance
“…Intriguingly, a nearly flat band can be also obtained by including the spin degrees of freedom in the presence of the spin-orbit coupling [22][23][24] or the dipolar interactions [25]. We note similar flattened quartic dispersion is also available in the shaken lattice [26].In this work, we describe a one-dimensional tunable optical zigzag lattice [27,28] and then analyse the geometric conversion from a zigzag into a sawtooth optical lattice that provides a nearly flat band [9,18]. Especially, a sawtooth lattice has attracted significant interest due to the flat band structure but the creation of tunable sawtooth geometry has not been proposed to our knowledge.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Intriguingly, a nearly flat band can be also obtained by including the spin degrees of freedom in the presence of the spin-orbit coupling [22][23][24] or the dipolar interactions [25]. We note similar flattened quartic dispersion is also available in the shaken lattice [26].In this work, we describe a one-dimensional tunable optical zigzag lattice [27,28] and then analyse the geometric conversion from a zigzag into a sawtooth optical lattice that provides a nearly flat band [9,18]. Especially, a sawtooth lattice has attracted significant interest due to the flat band structure but the creation of tunable sawtooth geometry has not been proposed to our knowledge.…”
mentioning
confidence: 74%
“…We analyse the band structure of the sawtooth and zigzag lattices for various lattice settings and provide a recipe for obtaining a nearly flat band in the sawtooth configuration. Besides the sawtooth lattice containing a flat band, a one-dimensional zigzag chain [27,28] also reveals particularly rich physics due to the interplay between frustration imposed by lattice geometry and two (three)-body interactions. Indeed, a chiral bosonic superfluid is expected in a zigzag lattice, which may become a Mott insulator even at small interactions [27,28].Creation of optical zigzag and sawtooth lattices An array of one-dimensional zigzag lattices can be created in twodimensional superlattice geometry.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The extra coupling between the legs of the ladder makes these systems unique, as a result of which, the quantum phase transitions are influenced substantially even in a simple model like the Bose-Hubbard ladder [25][26][27]. Also, the effect of kinetic frustration along with various interactions can lead to interesting new phases in ladder systems [28][29][30][31][32][33][34][35][36], which are not possible in one dimensional lattice systems. In recent years, it has been shown that novel quantum phases such as a trimer liquid and the devil's staircase can arise from atoms and molecules possessing long range interactions [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…The rich physics resulting from the interplay between frustration and interactions has attracted growing theoretical attention [15][16][17][18][19][20][21][22][23][24][25]. Recently, experiments on dynamically frustrated optical lattices in the presence of a synthetic gauge field have investigated the onset of chirality by observing the Meissner to vortex-phase transition [26].…”
Section: Introductionmentioning
confidence: 99%